Trichoderma afroharzianum B3R12: a potent biocontrol agent against Stromatinia cepivora, the causal agent of onion white rot - Ahmed M.M.A. Kasem; Younes M. Rashad; Nageh Fathy Abo-Dahab (Novel Research in Microbiology Journal, 2024)
Stromatinia cepivora (Berk.) Whetzel, the causal agent of onion white rot, is a devastating disease globally affecting onion crop production, leading to considerable losses. Control of S. cepivora is difficult due to its sclerotial high survival rate that can extend for decades in the soil. In this study, forty-nine Trichoderma species were isolated from the rhizosphere and tissues of 25 plant species collected from different sites across four Egyptian governorates. The antagonistic activity of all isolated Trichoderma strains was screened against S. cepivora BYAN1 in vitro. Microscopic examination showed that isolate B3R12 (identified as T. afroharzianum B3R12) has the greatest mycoparasitic level. Moreover, this isolate showed high in vitro inhibitory effect on S. cepivora BYAN1 growth by the production of both volatile and nonvolatile antifungal metabolites, recording inhibition of 74.32 % and 71.68 %, respectively. In the greenhouse experiment, T. afroharzianum B3R12 culture filtrate led to complete reduction in disease severity in the pretreated onion plants. In addition, pretreating onion plants with T. afroharzianum B3R12 enhanced several plant growth parameters and photosynthesis pigments, and increased total protein, carbohydrates, phenols, and flavonoid contents. Our results suggested that T. afroharzianum B3R12 represents a promising bioagent for biocontrol of onion white rot and promoting the plant growth; however, field evaluation in the future studies is necessary before the final recommendation.